The Effect of Live Yeast and Yeast Extracts Included in Lactation Diets on Antimicrobial Susceptibility of Fecal Escherichia coli in Sows - Jenna A. Chance; Jordan T. Gebhardt; Joel M DeRouchey; Raghavendra G. Amachawadi; Victor Ishengoma; T. G. Nagaraja; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Qing Kang; Joseph A. Loughmiller; Brian Hotze (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 27 sows (Line 241; DNA Genetics) were used in a study to evaluate the effect of feeding live yeast and yeast extracts to lactating sows on antimicrobial susceptibilities of fecalE. coli. Sows were blocked by BW and parity on d 110 of gestation and allotted to 1 of 2 dietary treatments. Dietary treatments consisted of a standard corn-soybean meal lactation diet or a diet that contained yeast-based pre- and probiotics (0.10% Actisaf Sc 47 HR+ and 0.025% SafMannan; Phileo by Lesaffre, Milwaukee, WI). Diets were fed from d 110 of gestation until weaning (approximately d 19). Sow fecal samples were collected to determine the antimicrobial susceptibility ofE. coliupon entry into the farrowing house and at weaning for each treatment. TheE. coliwas isolated from fecal samples, and species confirmation was accomplished by PCR detection ofuidAandclpBgenes. Microbroth dilution method was used to determine the minimal inhibitory concentrations (MIC) ofE. coliisolates to 14 different antimicrobials. Isolates were categorized as either susceptible, intermediate, or resistant based on Clinical and Laboratory Standards Institute guidelines (CLSI, 2018). An interaction (P = 0.026) of diet × sampling day was observed for cefoxitin where fecalE. coliisolates showed no significant differences (P= 0.237) in MIC values at entry, but sows fed the control diet had lower (P= 0.035) MIC values at weaning compared to sows fed yeast additives. There were no significant diet main effects (P>0.10) on the antimicrobial resistance (AMR) of fecalE. coli.There was an increased (P<0.02) trend towards resistance for 11 of the 14 antimicrobials over time. FecalE. coliisolates were resistant to tetracycline and ceftriaxone at weaning. All other isolates were considered susceptible or intermediate across sampling day. In conclusion, feeding live yeast and yeast extracts did not influence either sow or litter performance measurements or the AMR of fecalE. coliduring lactation except for cefoxitin, which had a higher MIC at the end of lactation when live yeast and yeast extracts were present in the diet.
Keywords: antimicrobial susceptibility; lactation; sows; yeast; yeast extracts